Design of a Compact GaN Power Amplifier With High Efficiency and Beyond Decade Bandwidth - Zhou, Han; Perez-Cisneros, Jose-Ramon; Langborn, Bjorn; Eriksson, Thomas; Fager, Christian (IEEE microwave and wireless components letters, 2022)
This letter presents a power amplifier (PA) design and network synthesis approach to achieve wideband and efficient performance with a very compact circuit size. A design method is presented in detail to convert a canonical filter-based high-order matching network to the proposed matching configuration with transistor parasitic and packaged elements absorption, and a compact passive network footprint. As a proof of concept, a prototype GaN HEMT PA is implemented. Starting from a fourth-order output network filter, the inductances and capacitance of the filter elements are re-organized to model, and thus absorb the output parasitics of the transistor, leading to a compact footprint with only four transmission lines. The measured results show that the prototype PA achieves an output power of 41.9-44.3 dBm and a 55%-74% drain efficiency, over a record-high decade bandwidth (0.35-3.55 GHz).